Działania wojsk ONUC wobec secesji Katangi (sierpień 1960-styczeń 1963) - Sołtysiak, Jakub (Acta Universitatis Lodziensis. Folia Historica, 2005)
The problem of the secession of Cathanga was the main part of the whole Congo’s crisis. Despite the efforts of the self-appointed president of the provincional government – Moisc Czombe, his separatist movement never gained official international recognition. UN Secretary-General Dag Hammarksjold managed to deploy UN Military Forces to Cathanga by means of diplomatic and peaceful methods, exclusively (12 August 1960). After the murder of the Congolese prime minister Patrice Lumumba, the Security Council in February 1961 called for removal from the Congo of all foregin military, paramilitary and advisory personnel not under the UN Command. After the adoption of the resolution UN soliders began to launch military operations against the Cathanga secessionist. Initially, Cathangese forces allied with mercenaries inflicted a defeat on UN Military Forces, and the United Nations was forced to negotiate terms at a disadvantage. Dag Hammarskjöld was killed in an airplane crash during these negotiations (17 September 1961). After rienforcements had arrived, the UN soliders launched another offensive, with air support, which destroyed the Cathangese secessionist movement (December 1962-Jannuary 1963). The UN Military Forces in Congo achieved definite aims; it had preserved the territorial integrity of the Congo and had removed all mercenaries from Cathanga. Nevertheles the minor principle of impartiality was broken when UN soliders used armed forces to put on concrete political solution in the minor war.